2016
DOI: 10.3889/oamjms.2016.034
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in Patients with Sickle Cell Disease in Tabuk

Abstract: BACKGROUND:Sickle cell disease is a common genetic disease in Saudi Arabia; it is an autosomal recessive disorder characterized by production of abnormal hemoglobin S and is associated with high morbidity and mortality. Acute splenic sequestration is a life-threatening complication for this disease. Prophylactic splenectomy is the only effective strategy for preventing future life-threatening episodes.AIM:The aim of this study was to study hospital records for all children aged 2 to 12 year old with Sickle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As the largest lymphatic organ, the spleen's functions are filtration of foreign matters from blood, antibody production, and bacteria control [1]. Removal of the spleen (splenectomy), mostly due to blunt splenic injury [2], hypersplenism [3,4], and functional hyposplenism [5][6][7] in some conditions (coeliac disease, inflammatory bowel disease, and sickle cell anemia) [8] can lead to several bacterial infections, including Klebsiella pneumoniae, Hemophilus influenzae, and Pseudomonas aeruginosa [5][6][7]. Although these bacteria could be found in the environment, they are encapsulated Gram-negative bacteria that could be found in the intestine [9].…”
Section: Introductionmentioning
confidence: 99%
“…As the largest lymphatic organ, the spleen's functions are filtration of foreign matters from blood, antibody production, and bacteria control [1]. Removal of the spleen (splenectomy), mostly due to blunt splenic injury [2], hypersplenism [3,4], and functional hyposplenism [5][6][7] in some conditions (coeliac disease, inflammatory bowel disease, and sickle cell anemia) [8] can lead to several bacterial infections, including Klebsiella pneumoniae, Hemophilus influenzae, and Pseudomonas aeruginosa [5][6][7]. Although these bacteria could be found in the environment, they are encapsulated Gram-negative bacteria that could be found in the intestine [9].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are concordant with those from a previous study in Oman indicating that patients with SCD and beta thalassemia are more likely to have splenectomy than other hematological disorders. 10 This finding may be explained by the relatively high prevalence of SCD in the Mediterranean Basin the Middle East. 11 , 12 Moreover, we found that most patients with SCD underwent splenectomy at less than 18 years of age or between 30 and 39 years of age, unlike those with beta and alpha thalassemia, who underwent the procedure before the age of 30.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection sheet was formulated according to several sources from the literature. 8 , 9 , 10 , 11 Descriptive statistics include the number, percentage, mean and standard deviation as appropriate. For comparisons, chi-square test or Fisher's exact test were applied.…”
Section: Methodsmentioning
confidence: 99%
“…A vaso-occlusive crisis is the most common presentation of SCD in patients, and it is responsible for major organ damage [ 5 ]. One of the earliest and most commonly affected organs is the spleen [ 8 ]. Splenic damage increases susceptibility to encapsulated organisms (for example, Streptococcus pneumoniae , Haemophilus influenzae , and Neisseria meningitidis ) and necessitates splenectomy and subsequent antibiotic prophylaxis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%